2014
DOI: 10.1080/10401334.2014.910464
|View full text |Cite
|
Sign up to set email alerts
|

Training Peer Instructors for a Combined Ultrasound/Physical Exam Curriculum

Abstract: Students' perception of peer instructors' teaching competency was equivalent to faculty instructors for the majority of sessions. Senior students who have completed an elective ultrasound rotation may serve as a useful resource for circumstances where the availability of skilled instructors is limited. However, further research is required to evaluate their effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 17 publications
2
80
0
2
Order By: Relevance
“…Peer-mentoring [126][127][128][129][130][131][132] In the course of evaluating articles which integrate POCUS in a novel way, peer mentoring emerged as a major theme in ultrasound education. In the peer mentoring studies reviewed, medical students in clinical or clerkship years (typically third or fourth year) teach preclinical medical students (first or second year).…”
Section: Learning Category-incorporation Of Ultrasound Into Teaching mentioning
confidence: 99%
“…Peer-mentoring [126][127][128][129][130][131][132] In the course of evaluating articles which integrate POCUS in a novel way, peer mentoring emerged as a major theme in ultrasound education. In the peer mentoring studies reviewed, medical students in clinical or clerkship years (typically third or fourth year) teach preclinical medical students (first or second year).…”
Section: Learning Category-incorporation Of Ultrasound Into Teaching mentioning
confidence: 99%
“…Ahn and colleagues compared student-tutors from 4 th year and found that students,who were trained with a four-week internship were rated higher than students with a two-week internship [18]. However, the satisfaction with the student-tutors is only an indirect measure of the learning outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The medical education literature has studied the feasibility and value of peer assessment, which can be used to evaluate clinical performance and competence, professionalism, interpersonal skills, and leadership ability. 11,12 There is evidence to suggest that students perform similarly on objective measures whether taught by student-teachers or faculty in certain circumstances. 1316 Curriculum faculty carefully select and train the residents who serve as table trainers, thus standardizing the hands-on experience.…”
Section: Discussionmentioning
confidence: 99%